African pentecostal theology : modality, disciplinarity, and decoloniality - Kgatle, Mookgo S. (Lanham, Maryland: Lexington Books, 2024)
"African Pentecostal Theology contributes new knowledge on how to study Pentecostal theology by exploring methodology, theoretical frameworks, and approaches in an African context. This book illustrates that Pentecostal theology, given its pneumatological approach, goes beyond conventional theological disciplines in transdisciplinary research"--
Includes bibliographical references (pages 227-266) and index.
Keywords: Pentecostalism -- Africa; Pentecostalism -- South Africa